Paradigmatic cases of pigmented lesions: How to not miss melanoma. Issue 12 (12th July 2016) - Farnetani, Francesca; Scope, Alon; Coco, Valeria; Guida, Stefania; Cesinaro, Anna Maria; Piana, Simonetta; Peris, Ketty; Pellacani, Giovanni; Longo, Caterina
Abstract: A large number of cases of melanoma exhibit clinical and dermoscopic clues leading to the correct diagnosis; however, sometimes melanoma can mimic benign melanocytic and non‐melanocytic lesions. We present a small series of melanomas in which additional clues provided by confocal microscopy increased the index of suspicion and prompted us to perform an excisional biopsy. Practical rules that are useful in difficult‐to‐diagnose melanomas are discussed.